PENGEMBANGAN LATIHAN SOAL KETERAMPILAN MEMBACA SMA KELAS XI SEMESTER II BERBASIS GAME BILLIARD ART - Jemali, Servasius; Samsul, Suwarno Imam (LATERNE, 2022)
Reading skills are the process of conveying messages by the author to the reader using written language. The delivery of the message is said to be successful if the reader can understand the contents of the text from the author. Readers should have a perception and understanding of the written text from the author, then give reaction to what he reads with integrity. Based on previous research by Rizka Miladyah Fauzan (Learning Outcomes of German Reading Skills with the Use of Media for Big Book Class X Students of SMAN 1 Sooko Mojokerto, 2018) stated that conventional delivery of material (lecture/recitation method) resulted in students feeling bored and tended to not involved in learning. He added that students have linguistic ability constraints (language, interest, motivation, and reading ability). The process of learning for the reading skills so far tends to be monotonous, where the teacher provides short texts that are tailored to the ability level of students. This method is less interesting for students, so they quickly feel bored and do not continue reading the texts. As a result, students do not understand the contents of the reading text and students are not involved in learning process. Therefore, teachers are required to be creative in delivering learning materials or in providing exercise. The utilization of science and technology development is one of many ways to improve students understanding quality. In this research, exercises on reading skills have been arranged by utilizing the development of science and technology, namely this Billiard Art Game which is operated through the Microsoft PowerPoint application. The formulation of the problem in the research for this scientific article is "what is the form of reading skills exercise for class XI semester 2 based on the Billiard Art Game?". The purpose of this study is to describe the form of reading skills exercise for class XI semester 2 based on the Billiard Art Game. The approach used in this research is a qualitative approach using the literature study method. The book Deutsch ist Einfach 2 and the internet are the data sources used in this research. The aspects analyzed in this research are the development of practice questions that are in accordance with the 2013 curriculum, the development of practice questions that are in accordance with Bloom's Taxonomy, and the development of practice questions that are in accordance with the Billiard Art Game media. The forms of reading exercises Essen und Trinken based on the Billiard Art Game produced in this study are interpersonal conversations or dialogues, pictures/food menu cards, and simple texts.